1999
DOI: 10.1177/135245859900500404
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of impairment in MS: discussion of the scales in use

Abstract: Accurate, efficient measurement of disease status has become a key issue in MS clinical practice and research. Despite some perceived problems, the Expanded Disability Status Scale (EDSS) remains the most widely used comprehensive measure of impairment. There is also a place for more restricted scales of impairment which focus on some aspects of neurological function in more detail than the EDSS e.g. measures of ambulation, arm function and cognitive function. Improvements in scales of impairment in the future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 15 publications
(12 reference statements)
1
35
0
1
Order By: Relevance
“…As reported in the literature, the lower scale values (0-4.0) are influenced by impairments detected by the neurological exam of eight functional systems, whereas the values above 4.0 are mainly based on walking ability and values above 6.0 mainly on patients' handicaps [21,[26][27][28]. Acquisition of EDSS steps 4 or above is considered a sufficient milestone because, once reached, MS inevitably progresses [29].…”
Section: Discussionmentioning
confidence: 95%
“…As reported in the literature, the lower scale values (0-4.0) are influenced by impairments detected by the neurological exam of eight functional systems, whereas the values above 4.0 are mainly based on walking ability and values above 6.0 mainly on patients' handicaps [21,[26][27][28]. Acquisition of EDSS steps 4 or above is considered a sufficient milestone because, once reached, MS inevitably progresses [29].…”
Section: Discussionmentioning
confidence: 95%
“…EDSS Kurtzke scale remains by far the most widely used scoring system in MS despite some perceived problems 20,21 . The development of combined analysis of clinical rating systems, envolving some aspects of neurological function in more detail than the EDSS, with more reliable and consistent MRI techniques may improve the evaluation of progression of the disease [20][21][22] . Kira et al 23 observed that DR2-associated DRB1*1501 allele and DRB5*0101 allele were associated with Western-type MS, but not with Asiantype MS, in their Japanese MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Disability evaluation among MS patients has given rise to the challenge of constructing instruments that are able to translate this clinical parameter of MS 13 .…”
Section: Reliability Testmentioning
confidence: 99%